Statins are not associated with a decrease in all cause mortality in a high-risk primary prevention setting. Issue 1 (11th January 2011) - Kaess, Bernhard M; Vasan, Ramachandran S
Abstract : Commentary on: Ray KK Seshasai SR Erqou S . Statins and all-cause mortality in high-risk primary prevention: a meta-analysis of 11 randomized controlled trials involving 65, 229 participants . Arch Intern Med 2010 ;170 :1024 –31 .